A proposed expansion plan of a palm oil plantation company for Aras Plantation Group (APG) - Indrasith Arasaradnam, Arasendran (2020)
This proposal is to seek the approval from the board to invest in a sum of RM100.2 million through borrowings to expand our plantation business overseas through the acquisition of a 5,000 Ha Greenfield plantation land in Indonesia. This proposal will expand our plantation land bank from 34,000 Ha to 39,000 Ha and give APG a new scope of international presence.